Legal Protection To Buyers Of Land In The Practice Of Buying And Selling Under The Hands Carried Out In The Presence Of The Village Head: (Case Study In Toroh District, Grobogan Regency) - Sunardi, Sunardi (FKIP, Universitas Palangka Raya, 2024)
Land purchase agreement under the hand is a land purchase agreement in Customary Law where the legal action is carried out in the form of transfer of rights with cash or non-cash payments (in part) carried out based on an agreement between the respective parties (seller and buyer) submitted by the head of Customs/Village Head.This study was conducted using empirical juridical method, a research approach in discussingthis problem bycaraanalyzingand combining legal materials (which are secondary data) with primary data obtained through research in the field.This study aims to determine what factors often causethe sale and purchase of land under the hands and also to determine how the legal protection to buyers in the practice of buying and selling land under the hands carried out in the presence of the village head, as well as what efforts should be made in providingkjusticebased on the law.This study uses the method of Field Research (Field Research) in which the authors sharpen the analysis to obtain data related to the practice of land purchase agreement under the hand in the presence of the village head in the District of Toroh, Grobogan. The results in this study indicate the relationship between buying and selling land under hand, the protection of the parties in obtaining legal certainty andimproving land administration governance.